The Experiences And Challenges In Caring For HIV/AIDS Patients: A Qualitative Exploration Among Muslim Family Caregivers In Malaysia - Pei Lin, Lua; Ramle, Abdullah; Ahmad Kashfi, A.R. (2014)
Objective: The family caregiver has a pivotal role in the management of HIV/AIDS patients and their well-being is consequently crucial as it could impact negatively on the quality of caregiving. This preliminary qualitative investigation intended to explore and describe the challenges and experiences of HIV/AIDS family caregivers in Terengganu, Malaysia. Methods: A convenient sample of family caregivers of HIV/AIDS patients who were aware of the diagnosis was enrolled. Recruitment was conducted in Hospital Sultanah Nur Zahirah, Kuala Terengganu, Malaysia and semi-structured interviews were used. Results: Results were transcribed into verbatim before being subjected to analysis. Twelve Muslim caregivers consented participation (age range = 18.0 - 81.0; female = 75.0%, mother/wife = 50.0%; married = 83.3%; ≤ primary school = 50.0%; and self-employed = 66.7%). The four major themes that emerged were challenges of caregiving, financial issues, stigma and discrimination, and support for caregivers. Additionally, caregivers did mention several positive aspects of their caregiving role including satisfaction from helping family member and improved family relationships. Conclusion: A variety of life aspects were negatively affected by caring for HIV patients, thus requiring a multidisciplinary approach to address such issues. ASEAN Journal of Psychiatry, Vol. 15 (2): July – December 2014: 120-130.